2010
DOI: 10.1167/10.11.22
|View full text |Cite
|
Sign up to set email alerts
|

Early biases and developmental changes in self-generated object views

Abstract: Object recognition depends on the seen views of objects. These views depend in part on the perceivers’ own actions as they select and show object views to themselves. The self-selection of object views from manual exploration of objects during infancy and childhood may be particularly informative about the human object recognition system and its development. Here, we report for the first time on the structure of object views generated by 12 to 36 month old children (N = 54) and for comparison adults (N = 17) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 59 publications
1
58
0
Order By: Relevance
“…The representation could be rotated to match the orientation of the object held by the child in each frame. The match yielded the three dimensional rotation of the test object in Euler angles (Kuipers, 2002; see Pereira et al, 2010, for details). From this output, a view was categorized as planar, using the procedure specified in Pereira et al (2010) if the front, top or side face of the object was within ± 11.25 degrees of parallel or perpendicular to the child’s line of sight.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The representation could be rotated to match the orientation of the object held by the child in each frame. The match yielded the three dimensional rotation of the test object in Euler angles (Kuipers, 2002; see Pereira et al, 2010, for details). From this output, a view was categorized as planar, using the procedure specified in Pereira et al (2010) if the front, top or side face of the object was within ± 11.25 degrees of parallel or perpendicular to the child’s line of sight.…”
Section: Methodsmentioning
confidence: 99%
“…This exploration may be a crucial step in the construction of stored object representations at a very early age, as manual exploration allows children to encode multiple views of objects that may not be acquired through observation alone (Pereira, James, Jones, & Smith, 2010; Perone, Madole, Ross-Sheehy, Carey, & Oakes, 2008; Ruff, 1984; Soska, Adolph, & Johnson, 2010). A crucial question, then, is whether manual exploration actually facilitates object recognition – a reflection of stored object representations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A similar method has previously been used by Billard (2011), Pereira, James, Jones, andSmith (2010), Smith, Yu, and Pereira (2011) and Yoshida and Smith (2008). The participating children in these studies were between 12 and 36 months of age.…”
Section: Head-mounted Gaze-trackersmentioning
confidence: 99%
“…Yet another active area of research has been concerned with the representation of objects used by children. Bloomington et al focused on viewing effects in object recognition and indicate that there are two viewing biases in children: planar views (i.e., views of objects held perpendicular to the line of sight) and the bias for upright orientation [27]. In [28] it has shown that children categorize superordinate classes based on part differences.…”
Section: Related Workmentioning
confidence: 99%